Prevention and Control of Legionella Infections in Mountain Huts – the New International Recommendation of the Medical Commission of the Union Internationale des Associations d’Alpinisme (UIAA MedCom) - Donegani, Enrico; Zotti, Carla; Ditommaso, Savina; Stefanetti, Maria; Windsor, Jeremy; Hillebrandt, David; Küpper, Thomas (Health Promotion & Physical Activity, 2020)
Legionnaire’s disease is a life threatening respiratory tract infection that is commonly associated with a stay in communal accommodations such as hotels, hostels, guesthouses and camping sites. In the European Alps and some other areas of the world mountain refuges and huts can sometimes accommodate over 100 guests in almost hotel like comfort. Such a “hut” may have cramped dormitories with multi-occupancy bunks and a basic water supply system possibly with hot water. Some will have showers. The water supply may be limited by the environment. As such these may pose a high risk for transmission of Legionellosis. In an environment of a hut which is more difficult to control than others. Unfortunately countries differ in their guidelines for the prevention of Legionnaire’s disease transmission within tourist accommodation. The aim of this paper is to propose a set of simple and pragmatic rules that can prevent the development of Legionella infections in mountain huts and other accommodations situated in the wilderness environment.